Student Satisfaction Towards Studies : Disciplinary, Demographic or Situation Related Variable? - Reunanen, Tero; Taatila, Vesa (AHFE International, 2022)
Students´ satisfaction towards studies is one of the most interesting information for universities in student questionnaires. How satisfied our students are and how we could enhance the satisfaction or guarantee that it will be high also in future. The reasons why some students are more satisfied towards their studies than others are always crucial to develop organization and studies. Sometimes the reasons can be explained more easier way than others and sometimes the reasons are more critical to organizations future than others. We have already shown in our last article that student satisfaction is correlating with personnel´s felt justice. In this research we are scrutinizing things which are affecting to students´ satisfaction deeper. We are studying how if and how the available demographic variables are affecting to the results of felt satisfaction. It will also be interesting to note if there are some demographic variables that do not have an effect on the felt justice.This research will be conducted by utilizing two different questionnaire tool Student barometer. Student barometer is a questionnaire for higher education students in Finland. It´s objectives are to provide data and information for researchers, research institutes education developers and decision makers in the institutes. Student barometer handles a variety of different matters from student life by asking students´ opinions from quality of studies to their civil life activities and their expectations of the future. Student barometer data consists of 2165 individual students as respondents in year 2019. They answered at most to 201 different questions and propositions. As the questionnaire was dynamic and depended partly on the previous answers, not all the questions and propositions were targeted to all of the students. Also the students’ responses were grouped by their degree programs, which makes it possible to compare the felt justice of the staff members to that of the students per each degree program. We are studying data sets from year 2016 to 2021. Data is analyzed with Excel and SPSS. Samples were taken from the data mass and were composed to a statistical model with excel spreadsheet. Students were grouped under schools and arithmetic averages and standard deviations were calculated to each proposition. After calculating the arithmetic averages further analysis was done with SPSS statistical analysis program. In SPSS proposition’s correlations were analyzed by single tailed Pearson correlation.The overall research question is: Is there a correlation between student satisfaction and available demographic variables. If so, how can this/these correlations be interpreted and what conclusions can be made? Future research aspects and practical recommendations will also be issued in the paper.
Keywords: fairness; leadership; management; Organizational behavior; satisfaction; fi=Tuotantotalous|en=Industrial Management|